Profile of plasmatic progesterone on pregnancy, and the postpartum estrus of Dasyprocta prymnolopha (Rodentia: Dasyproctidae) - Guimarães, Diva Anelie; Ohashi, Otavio Mitio; Singh, Michele; Vale, William (Revista de Biología Tropical, 2016)
The agouti (Dasyprocta sp.) is a hystricomorph rodent found in some regions of the Americas. It is an important cynegetic species, which indicates that the overhunting is a threat to their conservation. Very little is known about this wildlife in relation to what already has been studied in domestic animals. Thus, the knowledge on reproduction of wildlife becomes necessary and essential for the management and conservation of these natural resources. Specifically, studies regarding hormonal monitoring are important as a basic tool for research in modern reproductive biotechnology, and currently, there is no information on the progesterone changes during pregnancy of Dasyprocta sp., compared to other hystricomorphs. The aim of this study was to describe the profile of plasmatic progesterone during pregnancy, and report the restart of ovarian cycle in agouti after parturition. For this purpose, 18 black-rumped agoutis (Dasyprocta prymnolopha) born in captivity were used, and one or more consecutive pregnancies were observed. Copulation was confirmed by the presence of spermatozoa observed in the colpocytological examination. Blood samples were collected two times per week, and concentrations of progesterone, assessed in ten agoutis, were determined by radioimmunoassay. The onset of ovarian activity in six females was observed daily by colpocytological examination, starting on the seventh day postpartum. The gestational period observed in this study was 104.04 days (SD = 1.31) (101-106 days) (Number of cases, N = 26), and the interval between births was 126.03 days (SD = 18.40) (109-184 days). The plasmatic profile of progesterone during pregnancy showed a progressive increase from the 1st to the 5th week. The higher progesterone levels over this period (6.88 ng / mL, SD = 3.01) were detected in the 5th week. This value was similar (One-Way ANOVA, p > 0.05) to that observed in the 4th and 6th weeks, but was statistically different (One-Way ANOVA, p < 0.05) when compared to the other weeks. After the 6th week there was a progressive decrease in plasmatic progesterone levels. The animals showed a postpartum estrus of 12.04 days (SD= 4.29) (7-24 days) (N= 23). It was observed that 80.95 % (N= 19) of copulations during this period were fertile. This work contributed to understanding the dynamic changes in the progesterone levels during the pregnancy in agouti. Nevertheless, more studies are needed for a better appreciation of other endocrine and biological changes, in the mother and feto-placental unit of the agouti.